EMPLOYEE PERFORMANCE OF Y GENERATION IN BLORA REGENCY, CENTRAL JAVA - Darmanto, Susetyo; Supriyanto, Soni (Universitas Brawijaya, Indonesia, 2018)
Y Generation is a generation born between 1977 to 1994. This generation is often referred to as the echo boom generation and better known as the generation of technology. The purpose of this study is to analyze the effect of Emotional intelligence and Employee Creativity on the performance of Y generation employees at the Regional Secretariat of Blora Regency with job satisfaction as an intervening variable. The data used are primary data by taking samples of Y generation employees in the Regional Secretariat of Blora Regency as many as 46 respondents. Path analysis with SPSS 22 statistical program is used for data analysis. The overall hypothesis proposed receives Ha, which means the relationship between variables is positive and significant. In an effort to improve performance, Blora Regency Government can make efforts to increase Emotional intelligence and employee creativity. Job satisfaction is also proven to have a mediating role, so it can be a factor that plays a role in encouraging employee performance improvement.